Trauma in the Titicaca Basin, Bolivia (AD 1000–1450). (25th August 2015) - Juengst, S. L.; Chávez, S. J.; Hutchinson, D. L.; Mohr Chávez, K. L.
Abstract: The Late Intermediate Period (LIP) (AD 1000–1450) in the Andes was a time of turbulent political and social change as two major states, Wari and Tiwanaku, lost power. Increased rates of skeletal trauma in parts of Peru and Chile for this time period have been interpreted as increased interpersonal violence, perhaps as a result of the political vacuum left in the wake of state collapse. In the Titicaca Basin, people increasingly built defensive architecture on the northern lake shore; however, in the southern lake basin, people did not. Few skeletal remains have been excavated in the lake basin overall to corroborate an increase in violent activity or measure if violent activity was increasing for all populations. This paper reports the skeletal trauma for nine LIP individuals excavated from a common tomb on the Copacabana Peninsula in the southern Titicaca basin. This small sample is important for several reasons: (i) they are the only skeletal remains from the Copacabana Peninsula during the LIP; (ii) 100% of the sample population experienced traumatic injury, possibly because of interpersonal violence; and (iii) trauma was often survived. Copyright © 2015 John Wiley & Sons, Ltd.